The Role of Social Responsibility During the Corona Pandemic in Reinforcing the Sustainable Competitive Advantage: Identify Mediating Impact of Corporate Image “Case Study on Al-Arabi Group Company” - Al-Zuhairi, Amira (The Arab Journal of Administration, 2022)
This research aims to determine the impact of social responsibility in sustainable competitive advantage during the mediating impact of corporate image by applying it to Al-Arabi Group Company,. A questionnaire was designed to collect primary data from a sample of 381 workers whose validity and reliability were confirmed. A questionnaire was divided into four parts. The first part to measure social responsibility, the second part to measure corporate image, the third part to measure sustainable competitive advantage, and the fourth part to measure personal and functional variables. The research was designed based on three main hypotheses, and statistical tests showed a significant effect of social responsibility on the corporate image, also it was proven that there was a significant effect of the corporate image on the sustainable competitive advantage, and it was also proven that there was a significant effect of the company corporate image as a mediating variable in the relation between social responsibility and sustainable competitive advantage. The study provided many recommendations to reinforce social responsibility, corporate image, and sustainable competitive advantage.